Libraries of Babel: exploring library language and its suitability for the community. Issue 8 (3rd November 2017) - Fauchelle, Michael Alexander
Abstract : Purpose: The purpose of this paper is to examine the different aspects of language that are present in the signage, handouts and websites of public libraries. It discusses the extent to which this language reflects the varying demographics of library clients. Design/methodology/approach: This paper reports on a qualitative study, which took a document analysis approach and utilised an inductive-coding technique to analyse data collected from four lower North Island libraries in New Zealand. Findings: Five language aspects were identified from the collected data: monolingual, bilingual and multilingual language; language context; welcoming and prohibitive language; language consistency; and jargon. The nature and incidence of these aspects were evaluated for each of the four libraries. In some cases, the libraries achieve an accurate reflection of client demographics through their language. However, each library could make some changes to their use of language to better accommodate their distinct communities. Practical implications: This paper suggests that modifying library language to better reflect client demographics will contribute to an atmosphere of inclusion, welcome and acceptance. Such an atmosphere will promote information access for all members of the community. Recommendations for change are made, as well as suggestions for future research. Originality/value: This paper contributes to the body of knowledge on communication and language in libraries, particularly in a New Zealand context where there is a paucity of research on this topic. This paper benefits libraries and clients by identifying patterns, contrasts and potential improvements.